Prototyping a Serious Game to Enhance Indoor Air Quality Awareness Among the General Public in New Zealand - Baghaei Daemei A; Feng Z; Paes D; Lovreglio R (EDP Sciences, 2026)
Poor indoor air quality (IAQ) is directly linked to respiratory and cardiovascular diseases, allergies, and other health conditions. Mold significantly contributes to poor IAQ, which is closely related to various health issues, including respiratory and cardiovascular conditions. Raising public awareness about IAQ is essential for empowering individuals to adopt preventive measures. This study aims to develop a serious game designed to educate the general public on preventing mold growth in residential buildings in New Zealand. The game, developed using Articulate Storyline 360, engages users in identifying mold-prone areas in kitchens, bedrooms, and bathrooms, understanding mold formation factors, optimal temperature and humidity ranges, and applying effective mitigation strategies. A semi-structured interview involving 12 expert participants was conducted to validate the game’s content. Participants highlighted key mold-prone areas, including furniture near exterior walls, ceiling corners, and curtains, and emphasized the importance of managing moisture and cold surfaces to prevent mold growth. They recommended practical strategies such as wiping condensation, using extraction fans, and maintaining indoor humidity levels between 40–60% to mitigate mold risks effectively.